2007
DOI: 10.1063/1.2827325
|View full text |Cite
|
Sign up to set email alerts
|

Geometrization of Classical Wave Fields

Abstract: Geometrical model for material Dirac wave field and for Maxwell electromagnetic field is suggested where above fields are considered as propagating regions of the space itself with distorted euclidean geometry. It is shown that equations for these fields can be considered as relations describing the space topological defects. These defects, being closed topological manifolds, are embedded in the outer five-dimensional space, and observable objects appear to be intersections of above defects with the physical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In this work the geometrization of electromagnetic field is achieved via 5-dimensional approach that is free from abovementioned disadvantages. The principally new idea here is that we use as the starting point the geometrization of quantum objects, suggested earlier by the author [4][5][6][7][8][9]. This geometrization assumes that quantum particles can be considered as projections of the spatial topological defects moving in the space with dimensionality more than three.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work the geometrization of electromagnetic field is achieved via 5-dimensional approach that is free from abovementioned disadvantages. The principally new idea here is that we use as the starting point the geometrization of quantum objects, suggested earlier by the author [4][5][6][7][8][9]. This geometrization assumes that quantum particles can be considered as projections of the spatial topological defects moving in the space with dimensionality more than three.…”
Section: Introductionmentioning
confidence: 99%
“…This geometrization of electromagnetic field is the geometrization of the bose-field. Geometrization of the Dirac equation, suggested earlier by the author, can be considered as geometrization of the fermi-field, and we start with presentation of the main points of this geometrization [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It can be shown that due to pseudo-Euclidean metrics of the physical space-time such four-dimensional object represents moving topological defect of three-dimensional space and that this defect has wave-corpuscular and stochastic properties. And this gives an opportunity to identify such geometrical object with the quantum object, described by (1) [2,3] …”
Section: Foundations Of the Hypothesismentioning
confidence: 99%
“…Let us remind at first main points of the suggested geometrical interpretation of quantum mechanics [2,3]. The starting moment was the topological interpretation of Dirac's relativistic equation for free particle with spin ½. Symmetric form of this equation is [4] …”
Section: Foundations Of the Hypothesismentioning
confidence: 99%
“…This space looks, intuitively, as understandable one because its standards have dimensionality of length. On the other hand, time does not look understandable on the basis of This work is a соntinuation of author's investigations of possibility to explain physical phenomena by geometrical properties of the space-time [4] [5] [6] [7] [8]. In these investigations the idea was used about increasing dimensionality of our Euclidean space from three to four-the idea firstly used by Kaluza and then by Bergmann and Einstein in their attempts to geometrize electromagnetic field [9] [10].…”
Section: Introductionmentioning
confidence: 99%